The lunch line - Nagel, Karen Berman (New York : Scholastic Inc, 1996)
In the school cafeteria at lunchtime, Kim eyes all the tasty food and tries to figure out what she can buy with her dollars.
Keywords: Money -- Fiction; School lunchrooms, -- cafeterias -- Fiction; Food -- Fiction